Synthesis of bis[benzyl‐N′‐hydrazinecarbodithioato‐κ2N′, S]nickel(II) complex as a novel lead molecule for cancer treatment. (2nd October 2020) - Zahan, Ronok; Ahmed, Sinthyia; Sharmin, Tahmida; Halim, Mohammad A.; Rahi, Md. Sifat; Sheikh, Md. Chanmiya; Miyatake, Ryuta; Zangrando, Ennio; Naz, Tarannum; Islam, Md. Al‐Amin‐Al‐Azadul; Reza, Md Abu
Abstract : A novel bis[benzyl‐ N′ ‐hydrazinecarbodithioato‐ κ 2 N′, S ]nickel(II) complex was synthesized and characterized by means of various physical, chemical, and spectroscopic techniques. The X‐ray single crystal diffraction analysis indicated two independent close comparable bis‐chelated square planar complexes of trans ‐configuration, where S‐benzyl dithiocarbazate (SBDTC) ligand is coordinated via N, S‐donor set. The complex is able to inhibit Ehrlich ascites carcinoma (EAC) cell proliferation by 51.81% and 75.75%, with 0.3 and 50 mg kg −1 (dose adjusted) dose, respectively, administered intraperitoneally for five successive days in mice model. Apoptotic cell morphological changes were examined using optical and fluorescence microscopy techniques. Expression pattern of apoptosis regulatory genes in EAC cells treated with the synthesized nickel(II) complex for five consecutive days showed an increased expression of P 53, Bax, Cas‐8, Cas‐9, Cas‐3, Cyt‐c, and TNF‐α proapoptotic genes and decreased expression of antiapoptotic Bcl‐2 gene. The Ni(II) complex and Bleomycin (standard drug) were used in molecular docking coupled with molecular dynamics simulation studies with the aim to support the experimental results and to investigate the apoptotic effect towards the targeting apoptotic genes. Both experimental and computational studies reveal that the nickel(II) complex inhibits EAC cells growth successfully, suggesting a potential compound for cancer treatment. Abstract : Newly synthesized novel nickel(II) complex is very potent against EAC cancer cells both in vivo and in vitro conditions. Different parameters related to apoptosis validate its activity against cancer cells. Using several apoptotic genes expression helps to construct defined apoptotic pathway induced by nickel(II) complex. Additionally, the in silico approach like molecular docking coupled with molecular dynamics simulation is applied on the complex and a standard drug, Bleomycin, to support experimental findings and investigate chemo‐preventive effect towards targeting apoptotic genes.